Pengaruh Persepsi Siswa Mengenai Mata Pelajaran, Sikap Siswa Pada Guru Praktikum Akuntansi Jasa dan Dagang Terhadap Hasil Belajar Praktikum Akuntansi Jasa dan Dagang SMK di Sawahlunto dan Sijunjung - Gilang Oritaliano Putra; Agus Irianto (Jurnal Salingka Nagari, 2022)
Accounting and trade practicum subjects are one of the compulsory subjects in accounting majors at Vocational Schools where in general these subjects are considered by accounting students as difficult subjects, so this results in student learning outcomes being low. But for some students the subjects of practicum in accounting services and commerce is one of the subjects that most likes. But strangely the results of daily or summative test scores of average students in service accounting and trade practicum subjects are still low. Here the researchers took the locations of Sawahlunto Vocational School 1 and Sijunjung Vocational School where the best management business Vocational Schools are in Sawahlunto city and Sijunjung district and those who study here are average of all regions in Sawahlunto city and districts around Sawahlunto such as Tanah Datar and Sawahlunto.